ANALISI PERBANDINGAN PENGGUNAAN BANDWIDTH APLIKASI CONFERENSI ONLINE PADA WEBEX, GOOGLE MEET DAN ZOOM - Riko Gusjakal Muran; Yuan Lukito; Nugroho Agus Haryono (Fakultas Teknologi Informasi, 2021)
During this pandemic, conference calls or often called concall became a tool that was often used due to government regulations regarding the new COVID-19. Due to these regulations the concall application is commonly used by all agencies. Because of this, new users of concall applications haveincreased and many of these new users still do not understand which applications are suitable for the network in their area. Therefore, researchers made research to provide information about QoS (Quality Of Service) from several applications, namely Google Meet, Webex, and Zoom. In thisstudy, researchers conducted research with 20 PC clients who were given network boundaries of 0%, 25%, 50%, and 75% using the Queue Tree andPCQ methods. In the study, there were 3 stages in the process, namely preparation, data collection, and data processing. The variables used by researchers areDelay, Jitter, Packet Loss, and Throughput. These variables are retrieved using the Wireshark application on the client pc. In this study, researchers used the Queue Tree and PCQ methods to provide dynamic limits to the user and to be able to limit accordingly for each application hierarchically. In this study, it is known that some applications have a very significant decrease in performance when the confined network reaches 50% or more of the total network obtained by the researcher when conducting the research. Thus the researchers hope that with this study readers can get information about which applications are good for use in their respective areas which have different speeds.